Millennials' Perception of Start-Up Company Culture: Engagement, Motivation and Loyalty Moderated Termination - Fedrik Aldo Rico (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study examines the impact of corporate culture, work engagement, and work motivation on the loyalty of millennial employees in startup companies. Additionally, the research investigates how termination of employment (layoffs) can influence the relationship between these factors and employee loyalty. Data was collected from 250 millennial employees working in middle-level positions at startup companies in Jakarta. The results show that a positive corporate culture, high work engagement, and strong work motivation contribute to increased employee loyalty. However, layoffs can diminish the positive effects of work engagement and work motivation on loyalty. This research provides valuable insights for startup companies to develop strategies for enhancing millennial employee loyalty, especially in the face of challenges like layoffs.